Relationship between Crude Oil Prices and Stock Market: Evidence from India - Sharma, Ankit; Giri, Sasmita; Vardhan, Harsh; Surange, Sujeet; Shetty, Rohan; Shetty, Vishwaroop (International Journal of Energy Economics and Policy, 2018)
This paper estimates the linear interdependencies between international crude oil prices and stock market indices of India using weekly data spanning from Jan 2010 to Jan 2017 in a Vector Autoregressive framework. The time series used for the analysis are crude oil futures prices, Nifty Index, and BSE Energy Index. ADF and PP unit root tests reveal that all the time series are non-stationary at level and stationary at first difference. Cointegration test reveals the absence of cointegrating factor i.e. absence of long run relationship. VAR model captures all the time series as endogenous variables and independent variables are studied at two lags. Result shows that the Energy Index is very well explained by the lagged values of Crude oil futures prices, Nifty Index, and BSE Energy Index. Impulse response function reveals that crude oil prices are affected negatively when one standard deviation shocks are given to stock indices. Keywords: Crude oil, BSE Energy Index, Nifty, Vector Autoregression JEL Classifications: Q42, Q43